MODELING OF LANDSLIDE DEFORMATIONS UNDER THE ACTION OF GRAVITY - Lubkov М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nowadays, there are actual problems associated with destructive slope processes under the influence of gravity load. Indeed, gravitational slope processes, together with other erosion and tectonic processes, contribute a lot to the formation of the modern relief and at the same time very often complicate the rational using of the corresponding territory. Landslide processes can be distinguished among the most dangerous gravitational slope processes. These processes are characterized by widespread distribution and significant material losses and human casualties to which they lead. Due to its social importance and practical engineering significance, the problems of studying gravitational shear processes have a long history. Therefore, many works are devoted to these problems, but from another hand, the cases of strict mathematical and mechanical description and determination of certain quantitative mechanisms and criteria for the development of sliding gravitational processes have been considered in a rather limited way. In presented work on the base of variational finite-element method, we calculate the rotational deformation and failure criteria of a wide class of three-dimensional heterogeneous anticlinal geostructures under the gravity load conditions. The simulation results show that the shear deformation of anticlinal geostructures under the influence of gravity depends on the shape, size of the structure, and mechanical properties of the rocks that make up these geostructures. We have established that more compact geostructures are subjected to the smallest deformation. In the solid geostructures that retain elastic properties, the deformations are inversely proportional to the degree of rock stiffness, and a decreasing in the curvature radius of the geostructure leads to an inversely proportional increase in the deformation of the corresponding geostructure. We have shown that in order to maintain resistance to shear soil gravity failure, anticlinal geostructures cannot be completely composed of rocks softer than semi-solid dispersed soils. It was established that the resistance to shear gravity soil failure of heterogeneous anticlinal geostructures is mainly determined by the rigidity of the internal bearing rocks, while the influence of the stiffness of the external soft rocks is relatively insignificant and has a non-linear character.